Representasi Kearifan Lokal Budaya Timur Tengah dalam Film “Aladdin (2019)” Produksi Walt Disney Pictures - Nada Salsabila; Diah Ayu Candraningrum (Koneksi, 2020)
This research examines the representation of Middle Eastern culture local wisdom contained in the film "Aladdin 2019" produced by Walt Disney Pictures. This study aims to examine the cultural symbols of the Middle East. The research method used in this study is a qualitative method with Charles Sanders Peirce's semiotic analysis which divides the sign into three elements namely sign, object and interpretant. Semiotics is the science that discusses or examines the meaning of a sign. The results showed that Middle Eastern cultural symbols in the film "Aladdin 2019" were displayed through 10 scenes selected in the film. Cultural symbols of the Middle East are shown through the habits of the people kissing the right and left cheeks every time they meet relatives, riding camels to travel, livelihoods of people who trade, princess clothes Jasmine and Sultan, building architecture made of bricks and domes as decoration and art that displays traditional Middle Eastern musical instrument namely Gambus. Some interesting facts in the film one of which is the making of the city "Agrabah" as a shooting setting which is a fictitious city in England and property made of authentic jewelry.  Penelitian ini mengkaji mengenai representasi kearifan lokal budaya Timur Tengah yang terdapat dalam Film “Aladdin 2019” Produksi Walt Disney Pictures. Penelitian ini bertujuan untuk mengkaji simbol-simbol budaya Timur Tengah. Metode penelitian yang digunakan dalam penelitian ini adalah metode kualitatif dengan analisis semiotika Charles Sanders Peirce yang membagi tanda menjadi tiga elemen yaitu tanda, objek dan interpretan. Semiotika adalah ilmu yang membahas atau mengkaji mengenai pemaknaan dari sebuah tanda. Hasil penelitian menunjukkan bahwa simbol-simbol budaya Timur Tengah dalam Film “Aladdin 2019” ditampilkan melalui 10 scene yang dipilih dalam film tersebut. Simbol-simbol Budaya Timur Tengah ditunjukkan melalui kebiasaan masyarakat cium pipi kanan dan kiri setiap bertemu kerabat, menunggangi unta untuk bepergian, mata pencaharian masyarakat yang berdagang, pakaian putri Jasmine dan Sultan, arsitektur bangunan berasal dari batu bata dan kubah sebagai hiasan serta kesenian yang menampilkan alat musik tradisional Timur Tengah yaitu Gambus. Beberapa fakta menarik dalam film tersebut salah satunya adalah pembuatan kota “Agrabah” sebagai latar syuting yang merupakan kota fiktif di Inggris dan properti yang terbuat dari perhiasan asli.